O índice de desenvolvimento da educação do Estado de São Paulo: a materialização da racionalidade tecnológica - Gesqui, Luiz Carlos (2013)
The aim of this research was to analyze the reduction of the concept of educational quality due to indicators produced from large-scale assessments, specifically from the Education Development Index of the State of São Paulo (IDESP). It was used as the empirical field the set of state public schools of regular education from IDESP, from 2007 to 2011. This delimitation is specially justified by the fact that the indicator does not consider the academic production for the educational quality and it is imposed to the more than five thousand state public schools. The central hypothesis is that it is one more tool used by the technologic based industrial society to support the ideology that the educational quality can be measured and expressed in quantitative indicators. The method used was the exploratory, in the phases of gathering and organizing information, and after that, the analytical. The gathered information - from official documents and repoI1S, produced under the State Board of Education from São Paulo ( EE-SP), and from a survey applied to a set of 20 schools - was organized in charts, boards and pictures and analyzed concerning the relevant technical characteristics of a statistical indicator and also about the possible implications regarding the reduction of the educational quality concept, having as a reference the concepts of technological rationality, formation and ideology as they were formulated by Adorno, Horkheirner and Marcuse. The obtained results show that IDESP is limited on its formulation, on its production and on its outcomes and goals achieved because they do not express the fullness state of each school, as the results show little change in the performance and in the approving rates of the schools